Enhanced Parenchymal Arteriole Tone and Astrocyte Signaling Protect Neurovascular Coupling Mediated Parenchymal Arteriole Vasodilation in the Spontaneously Hypertensive Rat. Issue 7 (July 2015) - Iddings, Jennifer A; Kim, Ki Jung; Zhou, Yiqiang; Higashimori, Haruki; Filosa, Jessica A
Functional hyperemia is the regional increase in cerebral blood flow upon increases in neuronal activity which ensures that the metabolic demands of the neurons are met. Hypertension is known to impair the hyperemic response; however, the neurovascular coupling mechanisms by which this cerebrovascular dysfunction occurs have yet to be fully elucidated. To determine whether altered cortical parenchymal arteriole function or astrocyte signaling contribute to blunted neurovascular coupling in hypertension, we measured parenchymal arteriole reactivity and vascular smooth muscle cell Ca 2 + dynamics in cortical brain slices from normotensive Wistar Kyoto (WKY) and spontaneously hypertensive (SHR) rats. We found that vasoconstriction in response to the thromboxane A2 receptor agonist U46619 and basal vascular smooth muscle cell Ca 2+ oscillation frequency were significantly increased in parenchymal arterioles from SHR. In perfused and pressurized parenchymal arterioles, myogenic tone was significantly increased in SHR. Although K + -induced parenchymal arteriole dilations were similar in WKY and SHR, metabotropic glutamate receptor activation-induced parenchymal arteriole dilations were enhanced in SHR. Further, neuronal stimulation-evoked parenchymal arteriole dilations were similar in SHR and WKY. Our data indicate that neurovascular coupling is not impaired in SHR, at least at the level of the parenchymal arterioles.